Minimum information needed by prescribers. - Herxheimer, A (1978)
The prescriber needs adequate and concise information about each product that he uses, to allow him to obtain optimal effects while minimising harm. Neither the present UK data sheets nor their equivalents in other countries have succeeded in providing such information clearly or completely. This paper develops the proposals on the arrangement of drug information made in the WHO report "The selection of essential drugs." Three sets of minimum information (on tetracycline, propranolol, and aspirin) which illustrate this approach were compared with the manufacturers' data sheets: the latter were incomplete. The information content of our proposals was worked out with a group of clinical pharmacologists, general practitioners, and specialists, and we suggest that this approach should be extended to other drugs.